2015
DOI: 10.1007/s00417-015-2992-4
|View full text |Cite
|
Sign up to set email alerts
|

Medial rectus muscle elongation, a technique to treat very large-angle esotropia

Abstract: The MRE procedure seems an acceptable method to treat very large-angle ET with surgery on a lower number of muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
3
1
Order By: Relevance
“…Additionally, patients who received BMRE in our study had a smaller preoperative angle of deviation (85.83±9.25 PD) and were followed up for a longer period (24 months) compared with patients in the study by Ameri et al (94.1±19.33 PD). Moreover, the mean dose-response effect of BMRE in our study (5.45±0.39 PD/mm) was comparable with that reported by Ameri et al (5.53±0.67 PD/mm) 14 and notably better than that reported by Sood et al 13 …”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Additionally, patients who received BMRE in our study had a smaller preoperative angle of deviation (85.83±9.25 PD) and were followed up for a longer period (24 months) compared with patients in the study by Ameri et al (94.1±19.33 PD). Moreover, the mean dose-response effect of BMRE in our study (5.45±0.39 PD/mm) was comparable with that reported by Ameri et al (5.53±0.67 PD/mm) 14 and notably better than that reported by Sood et al 13 …”
Section: Discussionsupporting
confidence: 89%
“…The success rate of BMRE (83%) was higher than that of BMRR (50%) in our study and higher than that reported for BMRE by Ameri et al 14 (70%). It is notable that the success rate of BMRE in our study was also better than that reported for 3 horizontal muscle surgeries (62.4%).…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations